The Influence of Total Quality Management (TQM) and Service Quality (Servqual) on Customer Satisfaction of Netflix Services - Wahyudi Putera, Fajar; Ramdan Padmakusumah, Rizal (DINASTI RESEARCH, 2025)
This study aims to analyze the impact of Total Quality Management (TQM) and Service Quality (SERVQUAL) on customer satisfaction among Netflix users. Specifically, it investigates whether TQM affects customer satisfaction, whether SERVQUAL influences customer satisfaction, and whether both TQM and SERVQUAL together have an effect on customer satisfaction. The research employs a quantitative method with a sample size of 100 Netflix users from Bandung City. Data sources include primary data, obtained through questionnaires distributed to Netflix customers, and secondary data from existing documents, reports, and publications. Multiple regression analysis was used to process the data with SPSS. The findings show that TQM significantly affects customer satisfaction, with a t-value of 35.052 and a significance of 0.000 (p < 0.05), leading to the rejection of H0 and acceptance of H1. In contrast, SERVQUAL does not significantly affect customer satisfaction, with a t-value of 1.005 and a significance of 0.317 (p > 0.05), leading to the acceptance of H0 and rejection of H2. Additionally, the F-test reveals a significance of 0.000 (p < 0.05), indicating that both TQM and SERVQUAL simultaneously affect customer satisfaction.